Peri-Implant Bone Loss of External Hexagon and Morse Taper in Patients Wearing Immediately Loaded Overdentures - Melo,Laércio Almeida de (2017)
Abstract The aim of this study was to evaluate the peri-implant bone loss of External Hexagon (EH) and Morse Taper (MT) implants in patients wearing immediately loaded mandibular overdentures during a 1-year follow-up. This is a non-randomized controlled clinical trial including 18 MT and 22 EH implants. Periapical radiographs were taken after overdentures insertion and following 1 year. The peri-implant bone loss was assessed through digitalization and analysis of the radiographs in the software Corel DRAW X7. For this, measurement from implant platform to residual ridge at mesial and distal surfaces of each implant was conducted. The results showed high success rate in the groups EH (100%) and MT (94.4%). For peri-implant bone levels, it was found significant difference between the groups (p=0.032) and greater bone loss was observed in the group EH. In general, bone loss was 0.85mm (±0.82) for EH and 0.10mm (±1.0) for MT. It was concluded that greater bone loss occurred in the group EH in comparison to the group MT after a 1-year follow-up.